2012
DOI: 10.1021/la2042873
|View full text |Cite
|
Sign up to set email alerts
|

Water Adsorption on Clay Minerals As a Function of Relative Humidity: Application of BET and Freundlich Adsorption Models

Abstract: Water adsorption on kaolinite, illite, and montmorillonite clays was studied as a function of relative humidity (RH) at room temperature (298 K) using horizontal attenuated total reflectance (HATR) Fourier transform infrared (FTIR) spectroscopy equipped with a flow cell. The water content as a function of RH was modeled using the Brunauer, Emmett, and Teller (BET) and Freundlich adsorption isotherm models to provide complementary multilayer adsorption analysis of water uptake on the clays. A detailed analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
225
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(241 citation statements)
references
References 87 publications
12
225
3
1
Order By: Relevance
“…Figure 6 also shows the water adsorption isotherm of illite (lower panel, red curve, right y axis) reported by (Hatch et al, 2012). One possible explanation for the decrease in (N 2 O 5 ) with increasing RH is an increasing rate of deactivation of reactive surface groups (e.g.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Figure 6 also shows the water adsorption isotherm of illite (lower panel, red curve, right y axis) reported by (Hatch et al, 2012). One possible explanation for the decrease in (N 2 O 5 ) with increasing RH is an increasing rate of deactivation of reactive surface groups (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…However, as hydrolysis (solvation/ionization of N 2 O 5 to NO + 2 and NO − 3 ) will require more than one adjacent, surface-adsorbed H 2 O molecule, the latter will likely only take place under conditions of multi-layer adsorption, with an unknown RH threshold. In this context, we note that illite, with the general formula: M x [Si 6.8 (Hatch et al, 2012), has four OH groups in each structure unit. Previous experimental and theoretical work has shown that N 2 O 5 reaction on mineral surfaces is partially controlled by the availability of surface OH groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water isotherms in cellulose and pharmaceutical powders also show a water content of ~ 6−10 wt.% at moderate humidities, largely due to multilayers [69]. Clay minerals show multilayer adsorption above 15% RH and contents of 5−10 wt.% at 40% RH [70,71], and setup of capillary condensation at 80% RH [71]. Capillary condensation is settled by the radius r k of the liquid meniscus to be formed (Kelvin radius) given by r k = −V m /R g Tln(RH/100), where  is the liquid-gas surface tension, V m is the molar volume of the liquid and R g is the molar gas constant.…”
Section: Water In Colloidal Crystalsmentioning
confidence: 99%